Proton Pump Inhibitors Therapy in Children with Gastroesophageal Reflux - Aldo Reynaldo; Badriul Hegar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Proton pump inhibitors (PPI) has been widely used by clinicians to treat diseases that require suppression of gastric acid. PPI work by inhibiting the proton pump in gastric parietal cells.In adult patients, PPI hasbeen widely studied and showed effective results and safe. This result make PPI positioning as the first choice medicine in the treatment of diseases that require suppression of gastric acid. As the primary choice therapy, PPI administration has been increased not only in adults but also in children.PPI is often administered to children with a diagnosis of gastroesophageal reflux disease (GERD) which defined as symptoms or complications caused by gastroesophageal reflux (GER). GERD diagnosis in children is quite difficult, so it is common to find that diagnosis is established only by the basis of clinical symptoms, resulting in overdiagnosis and over-treatment of GERD. The use of PPI in children still needs further study andcan not be inferred based on adult studies. Inappropropriate PPI prescription without indication will increase side effect, risk and also harm the children. Thus, it is important to know the indications, side effects and safety of PPI therapy in children.Keywords: proton pump inhibitor, children, gastroesophageal reflux disease